External versus internal acquisition of new technology - Michael Hermes (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1992)
The development of new technologies and their application in new producta or processes are essential in today's competitive environment. Companies must make a Strategie decision concerning which new technologies they want to incorporate in their products/processes. Furthermore, they must decide how to acquire these new technologies. In-house research and development (R&D) is just one possible source of new technology. Another alternative would be to obtain a license, or to acquire a Company that has special expertise in the field of interest. "New", in this context, means new to the Company. If, for example, a license is available, the technology cannot be new to the world, and perhaps is not even new to the industry. Taking the perspective of the Company in the decision making process suggests defming "new" also in respect to the Company. The choice between different sources of new technology has a strong impact on the future competitive position of the Company. To have a supplier develop a new technology rather than developing it through one's own R&D efforts very probably lessens the necessary financial commitment (Teece 1976, p. 19), but at the same time deprives the Company of an opportunity to get acquainted with a new field of know-how, thus possibly weakening the future technological position of the Company in this field (Capon, Glazer 1987; Link et al. 1983; Pisano 1991)...
Keywords: 650; Leistungsbündel; Technologie; Industrieforschung; Theorie